Income redistribution through commodity programmes and the marginal welfare cost of taxation - Baharumshah, Ahmad Zubaidi (Penerbit Universiti Kebangsaan Malaysia, 1992)
Most economic welfare analysis of farm programmes are usually computed based on the assumption that the social opportunity cost of a dollar of public spending is equivalent to a dollar of private income. The approach simplifies the analysis but ignores the welfare cost of distortion caused by collection of taxes to finance public expenditure. This study shows that when the marginal opportunity cost of a dollar of government spending is greater than one dollar then the net social cost of farm programmes involving public expenditure is greater than typically estimated. Four policy options were considered in this paper and we showed that output subsidy is less pareto superior than tariff as commonly thought. Further, our analysis shows the pareto superior program is the one that combines production control couple with target prices and output subsidy.